1996
DOI: 10.1161/01.cir.93.9.1740
|View full text |Cite
|
Sign up to set email alerts
|

Oxidized LDL Decreases l -Arginine Uptake and Nitric Oxide Synthase Protein Expression in Human Platelets

Abstract: These observations indicate that the L-arginine-NO pathway is involved in the effects of ox-LDL on platelet function and that ox-LDL stimulates platelet function primarily by diminishing NO synthase expression as well as decreasing the uptake of L-arginine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
82
0
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(89 citation statements)
references
References 33 publications
6
82
0
1
Order By: Relevance
“…Our aim was to determine whether changes in NOS3 expression could account for the observed differences in NOS activation mediated by βAR and adenylyl cyclase. Western blotting of platelet lysates confirmed the presence of NOS3 in control and Type 2 diabetic subjects, a result consistent with previous studies [3,17,35]. No difference in basal NOS3 expression was found between platelets from control and Type 2 diabetic subjects.…”
Section: Discussionsupporting
confidence: 91%
“…Our aim was to determine whether changes in NOS3 expression could account for the observed differences in NOS activation mediated by βAR and adenylyl cyclase. Western blotting of platelet lysates confirmed the presence of NOS3 in control and Type 2 diabetic subjects, a result consistent with previous studies [3,17,35]. No difference in basal NOS3 expression was found between platelets from control and Type 2 diabetic subjects.…”
Section: Discussionsupporting
confidence: 91%
“…NO may also act as a neuroprotective or degradative agent, depending upon its concentration within the surrounding tissue [2,[14][15][16]. Aside from its aforementioned role in vasodilation, NO also plays a significant role in the modulation of platelet aggregation, smooth muscle cell proliferation, and LDL (low density lipoprotein) cholesterol oxidation within the cardiovascular system [1,[17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…In earlier studies, Chen et al (16) demonstrated in our laboratory that ox-LDL caused a concentration-dependent increase in thrombin-induced platelet aggregation and decreased activity. These effects were reversed by the pretreatment of platelets with L-arginine, the precursor (Fig.…”
Section: Effect On Oxidative Stressmentioning
confidence: 81%